Status Pengetahuan Gizi dan Pola Konsumsi Siswa - Siswi di SMPS Tunas Bangsa Kabupaten Bintan - Henricus Yayan Setyanto; Aprilia Nurcahyaning Rahayu; Devi Yanti (Journal on Education, 2025)
Teenagers are an age group that is vulnerable to nutritional problems due to unbalanced consumption patterns. Good nutritional knowledge plays an important role in establishing healthy eating patterns and preventing various health problems, such as obesity, anemia and non-communicable diseases. Factors that influence teenagers' consumption patterns include family environment, social media, eating habits, and the availability of food around them. Tunas Bangsa Middle School, which is located in a tourism area with limited access, is very vulnerable to having students who have low consumption patterns and knowledge. This research aims to obtain a mapping of nutritional knowledge categories and consumption patterns of female students. Based on the research results, it was found that the nutritional knowledge status of Tunas Bangsa Middle School students in recognizing the concept of adolescent nutrition, ingredients and types of food, as well as consumption patterns was in the very high category, this is in accordance with findings on consumption patterns where the frequency of consumption of junk food has a lower value than other types of food such as fruit and vegetables. Accessibility and availability of food are one of the factors that shape the unique consumption patterns of teenagers at Tunas Bangsa Middle School. Consuming chicken and fish is the most favorite food of all types of food available. It is hoped that teenagers can adopt a more balanced diet to support optimal growth and health.